Socio-economic aspects of migration in Russia - E. F. Nikitskaya; S. V. Grabchuk (Путеводитель предпринимателя)
Analysis of migration in Russian Federation has been actualized. There is actual statistics of migration in Russia. Analysis of migration has showed up unfavourable regions. The influence of migration to socioeconomic development in the regions has been described. The problems and the ways for improvement of migration policy has been presentated.